2008
DOI: 10.3168/jds.2008-1190
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Digital Dermatitis and Correlations with Locomotion, Production, Fertility Traits, and Longevity in Holstein-Friesian Dairy Cows

Abstract: Heritability of digital dermatitis (DD) and correlations between DD and type traits related to legs and feet were estimated from a linear animal model. Data comprised 93,391 national type evaluation records of pedigreed first-lactation Holstein-Friesian cows that calved from 2002 through 2006. At the time of classification, cows were housed in different housing systems (i.e., cubicles, straw yards, slatted or loafing yards) and on pasture. The type traits evaluated were locomotion score (LOCO), rear legs side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
6

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 25 publications
7
38
1
6
Order By: Relevance
“…The positive correlation of rear legs with ICF and negative with DO implied a shorter service period, which might be confirmed by the positive, favourable correlation between rear legs and NRc. These results partly agree with the findings of Zink et al (2011), who reported a positive genetic correlation between rear legs and both ICF and DO, but differ from the values published by Onyiro et al (2008), who obtained low negative correlations between rear legs and calving interval (CI) (0.09) and NRc (-0.11). CI and DO were closely related to each other because CI consisted of days open (DO) and gestation length and the latter showed very little variation (Jagusiak, 2005b).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The positive correlation of rear legs with ICF and negative with DO implied a shorter service period, which might be confirmed by the positive, favourable correlation between rear legs and NRc. These results partly agree with the findings of Zink et al (2011), who reported a positive genetic correlation between rear legs and both ICF and DO, but differ from the values published by Onyiro et al (2008), who obtained low negative correlations between rear legs and calving interval (CI) (0.09) and NRc (-0.11). CI and DO were closely related to each other because CI consisted of days open (DO) and gestation length and the latter showed very little variation (Jagusiak, 2005b).…”
Section: Resultssupporting
confidence: 82%
“…The correlations of foot angle with ICF and DO reported by Zink et al (2011) were very low, whereas Onyiro et al (2008) obtained a positive and also unfavourable genetic correlation of foot angle with CI (0.19) and a favourable correlation with NRc (0.14). The genetic correlation between body depth and NRc was negative and moderate; this means that daughters of bulls with a higher breeding value for body depth were also supposed to have a worse NRc.…”
Section: Resultsmentioning
confidence: 81%
“…This decrease can be explained by the increase in involuntary culling due to illnesses related to feet and legs. Onyiro et al (2008) found moderate genetic correlation with bone quality (-0.21) and high correlation between the side view of rear legs (-0.63) and digital dermatitis, reporting that cows without disease had good quality, flat bones and good set of the legs and feet, this being associated with increased herd longevity.…”
Section: Resultsmentioning
confidence: 99%
“…Estimated heritabilities are less than 0.15 for mastitis (e.g. Harder et al, 2006;Pérez-Cabal et al, 2009;Hinrichs et al, 2011) and 0.12 for CLDs (Koenig et al, 2005;van der Waaij et al, 2005;Onyiro et al, 2008;Laursen et al, 2009;Buch et al, 2011). However, next to production and fertility traits, health traits are still important in national breeding schemes, because even a small increment in disease rates has a serious influence on farm management costs (Koenig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%